Genetic response of Paspalum plicatulum to genome duplication - Weihmüller, Emilse (2014)
Paspalum plicatulum is a perennial rhizomatous grass with natural diploid and polyploid cytotypes. In this study, we investigated the occurrence of sequence polymorphisms arising immediately after genome autoduplication in this species. Two mixoploid plants (4C and 7D) were previously obtained through colchicine treatment of seeds generated by open pollination of a diploid plant (H14-2x). Diploid and tetraploid sectors from both mixoploids were dissected to generate two ploidy series (4C- 2x/4C-4x and 7D-2x/7D-4x). Molecular fingerprints were generated from the maternal plant H14-2x, both ploidy series (4C-2x/4C-4x and 7D-2x/7D-4x), and a tetraploid plant (C1) produced by selfing 7D-4x. Our results indicate that immediately after polyploidization P. plicatulum suffers genetic rearrangements affecting *28–38 % of the genome. Band gain and loss were equally prevalent at a statistically significant level. At least 5.62 % of the genome experimented recurrent genetic variation in a non-random basis with a confidence of 94.88 %. A significant proportion of novel bands (36 out of 195; 18.4 %) was detected in the C1 tetraploid plant. Half of these bands were not amplified in either H14-2x or 7D-4x, while the remainders were present in H14-2x but absent in 7D-4x. Our results indicate the occurrence of a considerable number of genetic changes in P. plicatulum immediately after polyploidization, some of which were recurrently detected in different independent events. Moreover, we confirmed that after polyploidization, lost ancestral alleles were spontaneously recovered in further generations, a phenomenon previously reported by other research groups.